Les relations texte / image dans l’édition numérique enrichie d’une œuvre littéraire - Arnaud Laborderie; Françoise Juhel (Itinéraires)
The French National Library, in partnership with Orange and the Voltaire Foundation, has designed an enhanced edition of Voltaire’s Candide, in the form of an iPad application associated to a website. This reissue of a classic book in a renewed format questions the usual closed and linear form of the book in favor of other approaches in confronting the text. The traditional access to content through the “Book” has been extended with two new ways of accessing content: the “World” and the “Garden.” In this remediation process, images have a new substantial importance with more than 400 sources: photographs of the manuscript itself and illustrations of the text, as well as thematic albums related to Candide. Such a wealth of sources is based on an educational choice: exploring the eighteenth century through Candide, enhancing the interpretation of the tale through the use of heritage resources, and initiating a methodology in discovering art and literature. By representing the steps in Candide’s journey on a map, the application invites the user into the imaginary tale through twelve thematic approaches, which associate Voltaire’s text with albums and anthologies, establishing an additional, image-based discourse.